La perspectiva cultural en el análisis de las organizaciones escolares. (2005)
Some points for a discussion about the public education have been presented in this article. The starting points  are the recognition of several aspects in this matter, such as the role awarded to the teachers, the technocratic logic of an  educational reality and at the same time, as a possibility to introduce some changes, the historie conscience, the sense of a political subject and the social construction.